Mobilizing Green Narratives: The Role of Instagram Reels in Indonesian Youth Environmental Activism - Febriana, Ajeng Iva Dwi; Rosmilawati, Srie (Indonesian Scientific Publication, 2024)
This study investigates the role of Instagram Reels in mobilizing environmental activism among Indonesian youth, focusing on the digital strategies of the Pandawara Group. Indonesia, with one of the highest Instagram user bases globally, presents a unique context where digital engagement intersects with climate concern. Utilizing a mixed-method approach, the research analyzes three Reels through engagement metrics (likes, comments, shares) and visual semiotic analysis to assess narrative structure, emotional appeal, and symbolic messaging. Findings reveal that Reels featuring problem-action-resolution narratives, community participation, and emotionally resonant imagery significantly boosted digital engagement and inspired offline clean-up initiatives. Over 620 tons of waste were removed from 187 locations, indicating a strong correlation between online interaction and real-world impact. Visual storytelling and hashtags enhanced message diffusion and identity formation among viewers, aligning with the theory of connective action. While Instagram's algorithmic biases and risk of slacktivism present challenges, the study outlines strategies to enhance digital activism's effectiveness. These include message consistency, participatory content design, educational components, and influencer collaborations. The research contributes to digital media and environmental communication scholarship by providing a replicable framework for youth-driven activism.